2018
DOI: 10.1016/j.jcat.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Acidity enhanced [Al]MCM-41 via ultrasonic irradiation for the Beckmann rearrangement of cyclohexanone oxime to ɛ-caprolactam

Abstract: Using solid acid catalysts to replace liquid acids in the liquid-phase Beckmann rearrangement of cyclohexanone oxime (CHO) into -caprolactam (CPL) is crucial for the environmentally friendly production of synthetic fibers, such as Nylon-6. In this work, we prepared aluminum-containing MCM-41 catalysts under ultrasonic irradiation with various Si/Al ratios for this purpose. Quantitative 1 H MAS NMR investigations show that ultrasonic irradiation significantly promotes the formation of active Brønsted acid site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 79 publications
5
39
0
Order By: Relevance
“…In conclusion, a remarkable synergy between two Al centers (Al V -Al IV or Al V -Al V ) close to the same SiOH group has been evidenced in flame-made amorphous silica-alumina (ASA) by 2D 27 Al and 1 H DQ-SQ NMR experiments, and analysis of the 3D spatial elemental distribution of Al and Si by APT. The study revealed that compared to the widely accepted model of one Al center per SiOH group with moderate strength (δ 13C = 213 ppm) 5 , two proximate Al centers can strongly decrease the electron density from a neighboring silanol oxygen and thereby can significantly boost its acid strength (with δ 13C = 227 ppm for CH 3 13 COCH 3 ) to a value higher than that of H-ZSM-5 (δ 13C = 223 ppm) 55 , or even reaching that of dealuminated zeolite HY (δ 13C = 228 ppm) 17 . These BAS with zeolitic strength have been evidenced by comparative H/D exchange experiments with C 6 D 6 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In conclusion, a remarkable synergy between two Al centers (Al V -Al IV or Al V -Al V ) close to the same SiOH group has been evidenced in flame-made amorphous silica-alumina (ASA) by 2D 27 Al and 1 H DQ-SQ NMR experiments, and analysis of the 3D spatial elemental distribution of Al and Si by APT. The study revealed that compared to the widely accepted model of one Al center per SiOH group with moderate strength (δ 13C = 213 ppm) 5 , two proximate Al centers can strongly decrease the electron density from a neighboring silanol oxygen and thereby can significantly boost its acid strength (with δ 13C = 227 ppm for CH 3 13 COCH 3 ) to a value higher than that of H-ZSM-5 (δ 13C = 223 ppm) 55 , or even reaching that of dealuminated zeolite HY (δ 13C = 228 ppm) 17 . These BAS with zeolitic strength have been evidenced by comparative H/D exchange experiments with C 6 D 6 .…”
Section: Discussionmentioning
confidence: 96%
“…S ilica-alumina materials, particularly crystalline zeolites and amorphous silica-aluminas (ASAs), are among the most popular solid acids that have been widely commercialized as efficient and environmentally friendly catalysts in the petrochemical industry 1 , and in bio-refinery 2 . These materials can provide Brønsted acid sites (BAS) with tunable density and strength, which facilitates the optimization of the surface acidity to promote a series of important industrial chemical reactions, through the formation of surface complexes or transition states by proton transfer from BAS to reactants [3][4][5][6] , such as to initialize C-H activation for hydrocarbon conversions [7][8][9][10][11][12] . Zeolites with strong Brønsted acidity, are of increasing importance in various sustainable processes, in the fields of biomass conversion, CO 2 capture and conversion, air-pollution remediation, and water purification 13 .…”
mentioning
confidence: 99%
“…Incorporation of Al atoms into the silica network/framework promotes the formation of Brønsted acid sites (BAS) . BAS can protonate hydrocarbons, forming carbocation intermediates, which promote important reactions, such as cracking, isomerization, alkylation, and aromatization . Steam treatment or Al‐exchange can introduce various Lewis acidic aluminum ions into zeolites, e. g. Al 3+ , AlOH 2+ , Al(OH) 2 + , while the defects in the alumina phase are related to the formation of Lewis acid sites (LAS) on the surface of ASAs due to the intrinsic inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4] BAS can protonate hydro-carbons, forming carbocation intermediates, which promote important reactions, such as cracking, isomerization, alkylation, and aromatization. [5][6][7] Steam treatment or Al-exchange can introduce various Lewis acidic aluminum ions into zeolites, e. g. Al 3 + , AlOH 2 + , Al(OH) 2 + , [8][9] while the defects in the alumina phase are related to the formation of Lewis acid sites (LAS) on the surface of ASAs due to the intrinsic inhomogeneity. LAS are able to abstract hydride or electron-rich groups (i. e. À OH) to form carbenium ions, and to drive the hydrocarbon reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research about the rearrangement reaction focuses on the process without producing ammonium sulfate, and relevant synthesis methods toward CPL have been continuously studied, which are vaporphase Beckmann rearrangement over solid catalysts [5][6][7][8] and liquid-phase Beckmann rearrangement over solid, [9][10][11][12] ionic liquid, [13][14][15][16] or organic catalysts. [17][18][19][20] However, the vapor-phase process suffers the problems of low selectivity and catalyst deactivation, and the current liquid-phase process is restricted by the problems of poor efficiency, low selectivity, and catalyst recycling, thereby limiting their industrial application.…”
Section: Introductionmentioning
confidence: 99%